Primary osteosarcoma of clivus: A short report. (August 2014) - Mohindra, Sandeep; Savardekar, Amey; Mahalingam, Shantanam S.; Mohindra, Satyawati; Vashista, Ramesh K.
Abstract Next to multiple myeloma, osteosarcoma is the commonest primary malignant neoplasm of skeletal system. These are aggressive tumours, composed of spindle cells producing osteoid and rarely occur in calvaria. The authors report a 55-year-male harbouring clival osteosarcoma, his clinical presentation, radiological findings, management and outcome.